Unemployment and the Social Safety Net during Transitions to a Market Economy: Evidence from the Czech and Slovak Republics - Ham, John C.; Švejnar, Jan; Terrell, Katherine (American Economic Review, 1998)
The Central and East European (CEE) countries are completing the first decade of a dramatic transition from a centrally planned economic system to a market system. Although economic outcomes have been diverse, all CEE countries (except for the Czech Republic) have experienced rapidly rising and persistently high unemployment rates, which have been accompanied by long spells of unemployment. By contrast, in the Czech Republic the unemployment rate has remained low and unemployment spells have been short (Table 1). The unemployment crisis in the CEE countries has contributed to a political backlash as disenchanted voters often ousted the first reform governments after a few years. This experience underscores the importance of two questions. First, why has the unemployment problem in the Czech Republic been much less severe? Second, how can economies in transition strike a balance between (i) reducing government intervention and introducing market incentives, and (ii) providing an adequate social safety net that ensures public support for the transition? In addition to being of academic interest, answers to these questions are essential for policy makers in the CEE countries, in Western governments, and at international institutions such as the World Bank and the International Monetary Fund.